The effect of rapid weight loss on the handgrip strength of national-level wrestlers - Carlo Rossi; Roberto Roklicer; Antonino Bianco; Marko Manojlovic; Barbara Gilic; Tatjana Trivic; Patrik Drid (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2022)
The effects of rapid weight loss (RWL) in combat sports athletes is an area that is not yet fully discovered. Therefore, the goal of this study was to determine the impact of weight loss on HGS (handgrip strength) in Greco-Roman wrestlers. This cross-over study included ten athletes examined for HGS during three time points for each hand. The first measurement - baseline (BL), was performed before weight reduction. The second measurement ‒ phase 1 (P1), was taken after high-intensity sports specific training (HISST) combined with RWL. In this phase, participants had to lose 5% of their body mass within three days, after which HISST was carried out (on day 3). The third measurement ‒ phase 2 (P2), was performed seven days after P1, which included HISST with no RWL. When comparing the HGS values, significantly higher values were observed only when P1 was compared with P2 for the left hand (p=0.039). This means that the grip was significantly stronger after RWL was conducted together with HISST. This research could be of great importance to combat sports coaches and athletes as it evaluates the effect of RWL on performance parameters. Therefore, the results of our study could serve to improve the wrestlers' weight-reduction plan.